Visual Inspection using Unmanned Aerial Vehicle (UAV): Case Study of Building Defects at Canteen and Surau Between SK Kampong Raja and SK Pekan Pagoh - Mohd Norhisham, Norellysha Fariha; Abdull Rahim, Nur Aqilah Iryani; Shamsudin, Nur Hafizah; Bujang, Hazirah; Mokhtar, Mardiha (Multidisciplinary Applied Research and Innovation, 2023)
Building inspection is essential in determining the condition of a building and is one of the most important aspects to conserve the building. To determine the defect, visual inspection was conducted as an early phase of building inspection. This research aims to study Sk Kampong Raja and Sk Pekan Pagoh defects at exterior structure and the roof structure especially at canteen and surau by using the drone, Phantom 3 Advanced. The obtained data were processed using the Condition Survey Protocol (CSP1) Matrix to determine the overall condition of the building. This study’s processes include site visits, planning and preparation prior to flight, data collection utilising a drone, image processing, and data analysis from images. The results of analysis for canteen and surau for two schools were analysed and refer to Figure 2 .The result shows, rating for canteen Sk Kampong Raja and Sk Pekan Pagoh are 5.3 and 5.4, while for surau Sk Kampong Raja 5.4 and surau Sk Pekan Pagoh 5.7 respectively. Overall the result shows that the canteen and surau building for both school were in fair condition.